Follow-up, residual- and recurrent disease after conization for CIN among women in Troms and Finnmark - Bjørnerem, Mathilde Seeger (UiT Norges arktiske universitet, 2017)
Objective: To evaluate adherence to the guidelines for follow-up after conization of Cervical Intraepithelial Neoplasia (CIN), and treatment outcome of high grade CIN (CIN2-3) among women living in Troms and Finnmark, North-Norway. Methods: Women aged 25-69 years treated for CIN for the first time in 2006-2011 were study participants (n=752). Recurrent disease was assessed among women who had two normal smears after conization. Residual disease was assessed among women not eligible for analysis of recurrent disease. We used Chi-Square for assessment of predictive factors of compliance and residual disease, and survival analysis to assess cumulative incidence of recurrent disease. Results: In total, 80.2% (n=603) had satisfactory compliance to follow-up guidelines after conization, independent of age. Only 10 women (1.3%) were lost to follow-up. Among those with abnormal smears after conization, 44 women (5.9%) were diagnosed with residual CIN2+ and 86% (n=38) of them were diagnosed within two years after conization. Cumulative incidence of recurrent disease was low during follow-up, with 0.8 (95% CI 0.0-1.6) at 42 months after treatment and 4.7 (95% CI 1.0-8.4) at 78 months per 100 women-years. Women with not free resection margin status at conization had significantly increased risk of residual- (P<0.01) and recurrent (P=0.004) CIN2+. Conclusions: Compliance to follow-up protocols after conization of CIN was satisfying. This study emphasizes the importance of discrimination between residual and recurrent disease. The majority of women with residual disease were identified within two years after treatment, however many would have been clarified earlier if cervical biopsy or diagnostic conization were performed sooner. The cumulative incidence of recurrent disease during 6.5 years follow-up after treatment was low (4.7 (95% CI 1.0-8.4) per 100 women-years at 78 months).